Modeling and analysis on low energy consumption foot trajectory for hydraulic actuated quadruped robot. (9th December 2021) - Sun, Yaru; Hua, Zisen; Li, Yibin; Hui, Chai; Li, Xianhua; Su, Bo
According to the energy consumption characteristics of hydraulic actuator, the valuable foot trajectory characterized by using segmented cubic spline interpolation curve in the swing phase is proposed firstly to reduce the energy consumption of quadruped robots, which is implemented by using controlling parameters tf to change the duration of leg raising and falling in one gait cycle, and then realized the directly control to the time ratio between the piston extension and retraction. Then, the total energy consumption of the hydraulic actuated quadruped robot SCalf-II is modeled. Meanwhile, the parameters of the foot trajectory that have a large impact on the energy consumption are determined. Finally, simulation analysis and verification experiments of the robot moving with constant speeds at the key parameters are performed. The results show that for the given foot trajectory, the optimization ranges of the gait cycle and duration of leg lifting from the lowest to highest are determined in which the energy required for the robot locomotion is at a relatively low level.